Investment ability: a catalyst for omni-channel supply chain integration - Alicia Neva Weber; Jacoba Orpha Cilliers (Cogent Business & Management, 2024)
Digital devices have revolutionized customer shopping behavior, giving rise to omni-channel retailing. Omni-channel retailing seamlessly integrates physical and digital channels, touchpoints, and supply chain operations. Owing to the rapidly evolving technology landscape, retailers struggle to discern the right investment approach to digitally transform their supply chains. Despite the widespread assumption that investment in supply chain integration (SCI) is vital for omni-channel retailing, empirical studies investigating the underlying mechanisms behind this process are limited. This research seeks to understand how and why investment ability catalyzes omni-channel SCI. Utilizing a two-phase abductive qualitative research design, Phase 1 involved 17 semi-structured interviews with senior managers from nine large South African omni-channel retailers. In Phase 2, content analysis of 40 integrated annual reports (IARs) from omni-channel retailers was conducted. This study identifies two crucial investment trade-off decisions that drive omni-channel SCI: financial and human resources. This demonstrates that strategically aligned investment ability fosters scalability and agility, playing a catalytic role in omni-channel SCI. The findings contribute valuable insights into omni-channel retailing and supply chain literature, providing practical guidance for managers navigating the complexities of investing in omni-channel SCI initiatives. These investment guidelines could accelerate the digital transformation and SCI processes for omni-channel retailers.
Keywords: 650; Omni-channel retailing; investment ability; supply chain integration; digital transformation; investment trade-off decisions; return on investment; supply chain management